Analysis of Nursing Care for Acute Pain with Swedish Massage Intervention in Post-Caesarean Section Patients - Rafika Nurul Aini; Devi Elisa Dostya Ainul Qoyyimah; Dini Kurniawati; Dina Ulfia (Health and Technology Journal (HTechJ), 2025)
Acute pain is a common problem experienced by patients after cesarean section, especially in cases with transverse fetal position that often require complex surgery. Effective and safe pain management is critical to improve the comfort and recovery of mothers. Nonpharmacological approaches such as Swedish massage are still underexplored in postpartum pain management but offer holistic therapeutic benefits. This study aims to evaluate the effectiveness of Swedish massage in reducing acute pain after cesarean section with transverse indication. A case study design was employed, involving a single participant. Swedish massage was administered for 15 minutes per session using five techniques (effleurage, petrissage, friction, tapotement, vibration). Pain intensity was measured using the Numeric Rating Scale (NRS). Results showed a decrease in pain from NRS 6 to NRS 3 after three sessions, indicating a 50% reduction in pain. Swedish massage has been shown to have positive effects by promoting relaxation and stimulating the release of endorphins, thereby reducing pain perception. These findings suggest that Swedish massage can be considered a safe, cost-effective, and nonpharmacological nursing intervention for post-cesarean section patients. Further research with a larger sample size is recommended to confirm its effectiveness and strengthen generalizability.